Electric Lamp Light Intensity System Using Blynk Based Internet of Things - Ramza, Harry; Saepurohman, Asep; Sofwan, Agus (TIME in Physics, 2025)
Internet of things (IoT) is a requirement that is being developed a lot in smart homes today. Currently, many technology developers create smart devices that can make human work easier. Smart home systems are one of them. In a smart home system, physical devices can communicate via the internet network or other near cable networks to monitor or control devices in a house or building. In order to be able to monitor or control the physical device is integrated with sensors and actuators. One implementation of a smart home is controlling the light intensity of the lights which can be adjusted using the sleader command on Blynk IoT which is installed on the smartphone. The aim of this research is for users to be able to control the light intensity of house lights by using the sleader command on the Blynk IoT application by house occupants. The method used in this research is IoT. IoT-based communication methods allow data exchange between devices. The result of this research is that a lighting control system can be built using Blynk IoT. A feature has been added to this system to control the electrical power that will enter the lamp, so that it can regulate the light intensity according to needs. The success of the system is influenced by the Blynk IoT response when giving a signal to the Node MCU 8266 and the DIMMER response when receiving a command signal from the NODE MCU8266.